Теоретические основы медицинской реабилитации = Theoretical foundations of medical rehabilitation - Gozhenko, E. A.; Badyin, I. Yu.; Gozhenko, A. I. (Journal of Education, Health and Sport, 2015)
Gozhenko E A, Badyin I Yu, Gozhenko A I. Теоретические основы медицинской реабилитации = Theoretical foundations of medical rehabilitation. Journal of Education, Health and Sport. 2015;5(5):213-224. ISSN 2391-8306. DOI 10.5281/zenodo.17591 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A213-224 https://pbn.nauka.gov.pl/works/559820 http://dx.doi.org/10.5281/zenodo.17591 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Теоретические основы медицинской реабилитации Theoretical Foundations of Medical Rehabilitation Е. А. Гоженко, И. Ю. Бадьин, А. И. Гоженко E A Gozhenko, I Yu Badyin, A I Gozhenko Украинский НИИ медицины транспорта, Одесса Ukrainian Research Institute for Medicine of Transport, Odessa Abstract In modern medicine, medical rehabilitation technology successfully developed and are an integral part of the effectiveness of the treatment of most diseases. The main objective in this case is to restore the structural and functional organization of organs and tissues to restore directed by discount disease functionality of an organism. It should be emphasized that the stimulation of the pathology of the compensation of disturbed functions in rehabilitation of existing technologies is always based on the inclusion of urgent adaptation mechanisms by increasing the intensity of functioning structures which, through subsequent actions (processes) are activated processes of hypertrophy and regeneration to ensure an increase in the number of functioning structures the basis of morphological changes are the basis of long-term mechanisms of adaptation / compensation, which are the basis of clinical adaptation. One of the promising methods of adaptation can be external bioprogramming. Keywords: medical rehabilitation, external bioprogramming, adaptation. В современной медицине технологии медицинской реабилитации успешно разрабатываются и являются неотъемлемой частью эффективности лечения большинства заболеваний. Основной задачей при этом является восстановление структурно-функциональной организации органов и тканей неправленое на восстановление сниженных при болезни функциональных возможностей организма. Стимуляция процессов компенсации нарушенных при патологии функций в существующих реабилитационных технологиях всегда основана на включении срочных механизмов адаптации за счет увеличения интенсивности функционирующих структур, которые посредством последующих воздействий (процессов) активируют процессы гипертрофии и регенерации обеспечивающих увеличению количества функционирующих структур на основе морфологических изменений, являющих базой долговременных механизмов адаптации/компенсации, которые являются основой клинической адаптации. Одним из перспективных методов адаптации может быть внешнее биопрограммирование. Ключевые слова: медицинская реабилитация, внешнее биопрограммирование, адаптация.